Low‐Field High‐Resolution PFG‐NMR to Predict the Size Distribution of Inner Droplets in Double Emulsions. Issue 1 (6th December 2020) - Khadem, Behnam; Parrott, Andrew; Nordon, Alison; Sheibat‐Othman, Nida
Abstract: In double emulsions, the inner and outer droplet size distribution (DSD) determines the quality of the double emulsion and is therefore essential to be measured. Low‐field high‐resolution pulsed‐field gradient nuclear magnetic resonance is used to measure the inner DSD in water‐in‐oil‐in‐water double emulsions. The Gaussian phase distribution approach is employed with a mixture of two normal distributions to predict bimodal inner droplets. This approach allows the prediction of the swelling of inner droplet during storage of double emulsions, and thus to validate a phenomenological population balance model estimating inner droplet swelling. Only a fraction of the inner droplets are found to swell during storage, due to differences in the Laplace pressure, thus leading to the formation of a bimodal size distribution of the inner droplets. Practical Applications : This methodology is useful to predict the evolution of double emulsions during storage, in a wide range of applications, such as food and pharmaceutical products. Abstract : Low‐field high‐resolution pulsed‐field gradient nuclear magnetic resonance is used to measure inner droplet size distribution in W/O/W double emulsions. The approach indicates the occurrence of swelling of inner droplet during storage and that only a fraction of inner droplets swell, thus leading to the formation of a bimodal size distribution.